A Critical Discourse Analysis of Representations of Bilateral Issues Concerning Malaysia and Singapore in Mainstream Newspaper Editorials - Ng, Siew Hua (2008)
The newspaper’s main role is to transmit news and it is often regarded as a source of ideological significance. One of the modes of transmitting the ideologies in the newspapers is through the editorials. The mainstream newspaper editorial uses diverse styles and discursive strategies to express the voice of the institution’s opinions and often the beliefs of any dominant group the institution represents. This study seeks to explore the ideological similarities and differences within the structure of editorials in the two widely regarded major means of providing news to the public in Malaysia and Singapore: the News Straits Times (NST) and Straits Times (ST) respectively using an analytical paradigm adapted from Wodak’s Discourse-historical approach theoretical framework and Fairclough’s Critical Discourse Analysis (CDA) framework. A qualitative historical research design was employed in this study to corroborate the findings. The findings were obtained from macro-structural and micro-linguistic analysis of selected editorials from both newspapers and intertextual and interdiscursive analysis of the historical background of events and bilateral issues involving both countries at different time frames from 1965 to 2005. A purposive sampling of one hundred and twenty (120) NST and ST editorials related to the bilateral relations between Malaysia and Singapore identified twenty nine (29) NST and twenty five (25) ST editorials written on the outstanding bilateral issues between 1973 to 2005. The results indicate that recontextualization of the outstanding bilateral issues involving both countries were evident in both mainstream newspaper editorials at certain time frames. Varied patterns of argumentation and linguistic representations particularly ingroup and out-group deictics of “we”, “us”, “them”, “they” or “their”, emotive verbs and negative lexis were used implicitly and explicitly in the two mainstream newspaper editorials at different time frames to voice each newspaper institution’s ideological stance. The findings showed that each institution’s stance related to the historical bilateral issues were representative of the voices of the dominant group or the government of each respective country. Both the NST and ST institutions played mediator roles between the government and public readers. As a result, only newsworthy events related to the bilateral issues were reported through selective choices of words. In this respect, it was found that language was a powerful and influential tool in both mainstream editorials. This adapted CDA theoretical framework used in the study has therefore brought about some levels of critical awareness and insights into the outstanding bilateral issues involving Malaysia and Singapore at different time frames from 1965 to 2005.